Тенденции развития мировой металлургии (2016 год) - Бабаченко, А.И.; Тубольцев, Л.Т.; Падун, Н.И. (Фундаментальные и прикладные проблемы черной металлургии, 2017)
Приведена динамика макроэкономических показателей мировой черной металлургии. Показано, что ситуация в экономике большинства регионов и стран мира в 2016 г. по сравнению с прошлыми годами все больше осложняется, Стратегическим направлением развития металлургии на среднесрочную перспективу является эволюционное изменение металлургических технологий. Показаны основные направления развития доменного, сталеплавильного и прокатного производства. Наведено динаміку макроекономічних показників світової чорної металургії. Показано, що ситуація в економіці більшості регіонів і країн світу в 2016 р у порівнянні з минулими роками все більше ускладнюється, Стратегічним напрямком розвитку металургії на середньострокову перспективу є еволюційна зміна металургійних технологій. Показано основні напрямки розвитку доменного, сталеплавильного і прокатного виробництва. This article presents the research on the structure of the world’s ferrous metallurgy and dynamics of its macroeconomic indices. In the article, we show that 2016 economic situation in the most regions and countries in the world became more complicated as compared with the previous years. This influences the manufacture of steel products as well. Thus, in the medium term, the main directions to develop in the metallurgical sphere are to be the evolutionary change of metallurgical technologies. . The basic directions of development is able to unite in a single whole the following: raw materials, power and energy carrying base, blast furnace, steel-making units, casting and rolling technologies as well as the conditions and prospects of the market.